A Subdivision Approach to the Approximate Solution of 3rd Order Boundary Value Problem - Manan, S. A.; Ghaffar, A.; Rizwan, M.; Rahman, G.; Kanwal, G. (Communications in Mathematics and Applications, 2018)
An algorithm to solve 3rd order boundary value problem is focused in this paper which is 8-point approximating scheme. It concludes the results with stability and convergence that is evaluated with the illustration of numerical example. This paper also contains the analysis of approximation properties for the mentioned collocation algorithm.